A revision of the subgenus Osmia (Diceratosmia), with descriptions of four new species (Hymenoptera, Megachilidae) - Griswold, Terry; Rightmyer, Molly G. (Zootaxa, 2017)
The eleven species of the North American subgenus Osmia (Diceratomsia) are revised, four of which are new: Osmia (Diceratosmia) exquisita, n. sp., from Honduras; Osmia (Diceratomia) gonzalezi, n. sp., and Osmia (Diceratomia) spinulifera, n. sp., from Mexico; and Osmia (Diceratomsia) lacunosa, n. sp., from the Bahamas. Diagnoses for the remaining seven species and a key to the males and females of all species are provided. We newly designate a neotype for Osmia botitena Cockerell, junior synonym of Osmia subfasciata Cresson, and remove from synonymy Osmia marilaunidii Cockerell, new status. In addition, we review the known nesting biology, floral hosts, and geographic range of each species.